2021
DOI: 10.11591/ijere.v10i4.22056
|View full text |Cite
|
Sign up to set email alerts
|

Perception of teaching performance in the virtual learning environment

Abstract: <span>This article aims to analyze the perception of the students of the professional school of business administration about the teaching performance in the virtual learning environment during the COVID-19 pandemic. When developing the research, it was determined that there is a good teaching performance, according to the perception of the students. However, it was identified that the factors of domain of the topic and class session management, present a better perception in this context of virtual lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…By understanding the challenges faced by teachers in using VLE, related parties such as school administrators and the ministry should provide adequate computer facilities and good internet access while technological devices should always be maintained by technicians to ease the learning process. Further, teachers need to be given early exposure to digital technology so that they are highly motivated and fit to use technological innovations [37]. E-learning will be successful if teachers have the appropriate technological knowledge, training, and time to practice the applications [38].…”
Section: Discussionmentioning
confidence: 99%
“…By understanding the challenges faced by teachers in using VLE, related parties such as school administrators and the ministry should provide adequate computer facilities and good internet access while technological devices should always be maintained by technicians to ease the learning process. Further, teachers need to be given early exposure to digital technology so that they are highly motivated and fit to use technological innovations [37]. E-learning will be successful if teachers have the appropriate technological knowledge, training, and time to practice the applications [38].…”
Section: Discussionmentioning
confidence: 99%
“…Learning analytics has developed significantly over the last decade and has contributed substantially to understanding online student engagement [13], [14]. Researchers have employed data analytics and machine learning techniques to examine patterns of student engagement and performance in virtual environments [15]. An exciting advance has been the development of recommendation systems based on learning analytics, which use advanced algorithms to analyze students' browsing and participation behaviors, offering personalized recommendations for resources and activities [16].…”
Section: A Review Of Similar Workmentioning
confidence: 99%
“…They can also provide appropriate motivational guidance through external experts while continuing online learning. Furthermore, research has shown that there is a significant correlation between student motivation and teacher performance [31]. As a result, students' motivation would lead to a better learning environment and better achievement of learning outcomes.…”
Section: Factors Determining the Effectiveness Of Ertmentioning
confidence: 99%